Interest Rate Pass‑through and Monetary Policy Transmission in SADC and EAC Countries: Implications for Monetary Union - Damilola Oyetade; Ephrem Habtemichael Redda; Paul‑Francois Muzindutsi (Comparative Economic Research)
Southern African Development Community (SADC) and East African Community (EAC) countries are exploring the feasibility of establishing a monetary union. This study assesses the economic integration in the two blocs, using the interest rate pass‑through mechanism to determine the convergence of interest rates in the two regions. This study evaluates the potential for forming a monetary union using the panel autoregressive distributive lag model (PARDL) with monthly data from January 2000 to December 2022, including central bank and retail bank interest rates. The dynamic common correlated effects (DCCE) results suggest that the complete interest pass‑through to retail bank rates does not hold for the two blocs. Secondly, there are varying speeds of adjustment for banking rates in response to changes in policy rates. In addition, the incomplete interest‑rate pass‑through for the two blocs indicates the presence of banking market imperfections, weak banking asset quality, and information asymmetries, which are more pronounced in the EAC. Monetary policymakers should implement measures to enhance the efficiency and competitiveness of their financial systems to minimise these imperfections.